Forestry Insights of Some Asian and European Countries: National Forest Harvesting Strategies and New Approaches - Lotfalian, Majid; Harpole, W Stanley; Pentek, Tibor; Akay, Abdullah Emin; Poršinsky, Tomislav (My University, 2023)
As forestry approaches have been formed according to the demands and aspirations of the society, the forest sector implies different concerns such as social, economic, and environmental. Harvesting and extraction of wood at low cost, protection of stands against degradation and changes in land use, proper implementation of afforestation and forest extension, conservation of endemic species, preservation of soil, providing jobs, and supporting national and domestic development have a different priority for foresters, depending on the time and area conditions. Of course, all of these have always been discussed by the shareholders in the forest sector with the main attention to forest sustainability. However, the question is: Are forestry approaches compatible with the changes in the world today? With increasing environmental concerns, as discussed at the Glasgow 2021 Conference, the importance of forests and their protection has doubled, and it seems that forestry practices in the world need a new approach. In addition to climate change, increasing human population and regional and global economic changes affect the use of forests and the form of forest management and utilization. This paper aims to take an analytical look at this issue and examine the current situation in five countries (Iran, Germany, Croatia, Turkiye and Italy). It was also targeted with the help of the DPSIR Framework to elaborate on the social consequences of the situation, and an analysis was presented about what to do or not. This paper emphasizes that forest managers and policymakers need to modify and adapt the plans and methods in a way that is appropriate to the progress of time and its changes, while protecting forests and ensuring their sustainability, limiting non-professionals from involving directly in the decision-making process.
Keywords: Climate change; Conservation; Sustainable Forest Management; DPSIR; Forest Operations; Forest Policy